Penegakan Hukum oleh Kepolisian Sektor Kateman terhadap Perkara Tindak Pidana Pencurian: Studi di Wilayah Hukum Kepolisian Sektor Kateman - Satria Satria; Fitri Wahyuni; KMS. Novyar Satriawan Fikri (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Law enforcement against theft is a primary responsibility of the Indonesian National Police in maintaining public order and ensuring legal certainty. This study examines the law enforcement process carried out by the Kateman Sector Police in handling theft cases and identifies the obstacles encountered in its implementation. Using an empirical legal research method with a sociological approach, the study collected primary data through interviews with investigators and secondary data from legislation, books, journals, and relevant documents. Data were analyzed descriptively using a qualitative method. The findings show that law enforcement is conducted through receiving reports, investigations, evidence collection, suspect identification, and submission of case files to the public prosecutor in accordance with applicable laws. However, its implementation is constrained by limited human resources, inadequate facilities, difficulties in obtaining evidence, low public participation, and increasingly sophisticated criminal methods. Strengthening police capacity, improving facilities, and enhancing cooperation between the police and the community are essential to achieving more effective, professional, and fair law enforcement.